Natural Disaster, Local Knowledge, and Local Policy in a Small City in Southeast Sulawesi, Indonesia - Idaman Idaman; Handrawan Handrawan; Indra Rahayu Setiawati; Irwansyah; Nisa Nasyra Rezki (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Konawe Selatan is one of the regions with a high intensity of natural disasters in Southeast Sulawesi. From time to time, natural disasters in Konawe Selatan seem to have become a